Incidence and use of resources for chickenpox and herpes zoster in Latin America and the Caribbean--a systematic review and meta-analysis - Bardach, Ariel; Cafferata, María Luisa; Klein, Karen; Cormick, Gabriela; Gibbons, Luz; Ruvinsky, Silvina (The Pediatric infectious disease journal, 2012)
Varicella-zoster virus causes chickenpox and herpes zoster. More than 90% of varicella cases occur in childhood. The aim of this study was to gather all relevant information on epidemiology and resource use in Latin America and the Caribbean since 2000. Epidemiologic studies published since 2000 with at least 50 cases of varicella or herpes zoster, or at least 10 cases of congenital disease were included. Gray literature was also searched. Outcomes included incidence, admission rate, mortality and case-fatality ratio. Use of resources and both direct and indirect costs associated were extracted. From the 495 records identified, 23 were included in the meta-analysis to report varicella-zoster virus outcomes and 3 in the herpes zoster analysis. The global pooled varicella incidence in subjects under 15 years of age was 42.9 cases per 1000 individuals per year (95% confidence interval: 26.9-58.9); children under 5 years of age were the most affected. Pooled general admission rate was 3.5 per 100,000 population (95% confidence interval: 2.9-4.1) and median hospitalization was 5-9 days. The most common varicella complications reported in studies were skin infections (3-61%), followed by respiratory infections (0-15%) and neurologic problems (1-5%). Direct costs averaged (2011/international dollar [I$]) $2040 per admission (range, I$ 298-5369) and I$70 per clinical visit (range, 11-188 I$). Limited information was available on the outcomes studied. Improvements in the surveillance of ambulatory cases are required to obtain a better epidemiologic picture. As of 2011, only 2 countries introduced the vaccine in national immunization programs in Latin America and the Caribbean.